2018
DOI: 10.1016/j.coelec.2017.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Polymer light-emitting electrochemical cells—Recent advances and future trends

Abstract: Polymer light-emitting electrochemical cells (PLECs) are electroluminescent devices whose operation involves both ionic and electronic charges. A key reaction in PLEC is the electrochemical doping of the light emitter, a luminescent polymer, which eventually leads to the formation of a light emitting p-n or p-i-n junction in the interior of the cell. This review opens with a general introduction to the operating mechanism of PLECs. This is followed by a summary of key advancements in the field in the last two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 69 publications
(70 reference statements)
0
41
0
Order By: Relevance
“…Thisd elay between the onseto f current flow and the onset of photocurrent is consistentw ith the electrochemical doping model( ECD) of LECs, where the formation of the luminescent p-i-n junction is preceded by the injectiono fe lectrons and holes at the anode and cathode, re-spectively. [49] Once the p-n junctioni sf ormed,s ubsequent injected charges recombiner adiatively in the insulating region, leadingt ot he emission of light via electroluminescence. The EL intensity increased steadily from the onset potential, reaching am aximum of 800 nA at 12.5 V. The luminous efficiency of the GQD-LEC was calculated to be 0.14 %r elative to a Ru(bpy) 3 2 + standard in the annihilation pathway.W hen ac onstant current of 1mAw as used to drive the LEC (Figure 7b)a gradualincrease in both the potential and electroluminescence intensity was observed, indicating that the resistance between the electrodes is increasing as device operation continues, and the luminescent junctionm ay not be particularly stable.…”
Section: Gqd-based Light-emitting Electrochemical Cellsmentioning
confidence: 99%
“…Thisd elay between the onseto f current flow and the onset of photocurrent is consistentw ith the electrochemical doping model( ECD) of LECs, where the formation of the luminescent p-i-n junction is preceded by the injectiono fe lectrons and holes at the anode and cathode, re-spectively. [49] Once the p-n junctioni sf ormed,s ubsequent injected charges recombiner adiatively in the insulating region, leadingt ot he emission of light via electroluminescence. The EL intensity increased steadily from the onset potential, reaching am aximum of 800 nA at 12.5 V. The luminous efficiency of the GQD-LEC was calculated to be 0.14 %r elative to a Ru(bpy) 3 2 + standard in the annihilation pathway.W hen ac onstant current of 1mAw as used to drive the LEC (Figure 7b)a gradualincrease in both the potential and electroluminescence intensity was observed, indicating that the resistance between the electrodes is increasing as device operation continues, and the luminescent junctionm ay not be particularly stable.…”
Section: Gqd-based Light-emitting Electrochemical Cellsmentioning
confidence: 99%
“…Light emitting diodes (LEDs) have been at the forefront of lighting technology recently due to their decreased energy consumption over compact fluorescent and incandescent lighting technologies. LEDs are conventionally created by depositing many subsequent layers on a substrate in an inert atmosphere (Zhang et al, 2013 ; Gao, 2018 ; Kusamoto and Nishihara, 2018 ; Yang et al, 2019 ). Reducing the number of layers and removing the need for an inert atmosphere can drastically reduce manufacturing costs and operating voltages.…”
Section: Introductionmentioning
confidence: 99%
“…LECs conventionally comprise of two electrodes sandwiching a light-emitting layer that is responsible for both charge transport and light emission (Fresta and Costa, 2017 ). The light-emitting layer typically consists of a polymer and a salt with an incorporated light emitter which organizes itself into a p-i-n junction when an external bias is applied (Gao, 2018 ). The polymer electrolyte reduces bulk and contact resistance over LEDs, allowing for air-stable and thicker electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] However, their wide implementation must also take into account not only a simple device architecture and a low-cost solvent-based fabrication process, 5,6 but also an excellent self-stability upon storage and mechanical stress 7 and the right operating conditions to meet the performance criteria for each application. 3,[7][8][9][10][11][12][13][14][15] In this context, the effect of the temperature in the LEC performance is a critical aspect that has barely been considered in the literature up to date. [16][17][18] In brief, Friend et al reported on the reversible color changes in LECs based on copper(I) complexes upon externally applying temperature, 16 while Slinker and co-workers nicely studied the relationship between the thermal stability of LECs with iridium(III) and ruthenium(II) complexes and the presence of their degradative metal centered excited states.…”
Section: Introductionmentioning
confidence: 99%